Competition and Consumer Behavior in the Context of the Digital Economy - Elena-Mădălina Vătămănescu; Bogdan Gabriel Nistoreanu; Andreea Mitan (Amfiteatru Economic Journal, 2017)
The current paper aims to investigate the relation between competit ion and online purchasing decision-making, integrating consumer protection awareness and the corresponding consumer behavior as mediators. The focus is on both subjective and objective measures related to the level of consumer awareness and action in a fast -growing competition, potentiated by the digital economy. In order to investigate the relations between the aforementioned concepts, a questionnaire-based survey was conducted, using a sample of 257 students from three top Romanian universities. Based upon the theoretical directions presented in the literature review, a conceptual model was elaborated and tested by employing a part ial least squares structural equation modeling technique. As the examination of the structural model indicated, online purchasing decision -making is indirectly influenced by the high competition in the digital economy, by means of consumer protection awareness and consumer protection behavior. At this level, the analyzed factors, namely the competition in the digital economy, the consumer protection awareness and the consumer behavior with respect to the consumer protection policies, explain over 16% in the variance of the online purchasing decision-making.
Keywords: D18; F12; F68; 330; consumer protection; competition; digital economy; online purchasing decision-making